Economic Literacy amongst the Secondary School Teachers in Perak Malaysia - Yeop, Nek Kamal; ., Norasibah Abdul Jalil (Information Management and Business Review, 2010)
The aim of the study is to determine the relationship between economics education exposure, saving, expenditure, investment and economics literacy amongst teachers in secondary schools in Perak. The theoretical framework was designed based on the literature and hence five hypotheses for the study were formulated. The samples were selected by quota sampling methods. The data were collected by distributing structured 35 items questionnaires to 100 teachers in secondary schools in eight districts in Perak. The instrument was adapted form Leader Behaviour Description Questionnaires which were used to measure economic literacy. Only 60 questionnaires were returned and analysed which gave 60% respond rate. Data collected were sorted out and keyed in into SPSS version 17. The data were analysed using descriptive and inferential statistics to answer the research questions. The result of the analyses showed that there was significant relationship between economics education and its predictors. Together the independent variables explained 81.7% of the variance in the dependent variables. The remaining 18.3% was due to unidentified variables. In relation to that, the study had contributed some knowledge about the understanding of economic of literacy. For future research, it is recommended that other than the above variables might influence economic literacy perhaps with a bigger samples and wider scope.